The Relationship Between Realization Of Apbd And Regional Economic Growth: An Empirical Study In Makassar City - Fitriani Fitriani; Haliah Haliah; Nirwana Nirwana (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the relationship between the realization of the Regional Revenue and Expenditure Budget (APBD) and economic growth in Makassar City during the 2020–2023 period. The approach used is quantitative with descriptive statistical analysis methods, Pearson correlation, and simple linear regression. Secondary data were obtained from BPS, the APBD Realization Report, and documents from the Ministry of Finance and Bappeda. The results of the study show that regional spending increased significantly from IDR 4.21 trillion in 2020 to IDR 5.64 trillion in 2023. On the other hand, economic growth showed a post-pandemic recovery with an average annual growth of 3.25%. The correlation test shows an r value of 0.91, which indicates a very strong positive relationship between regional spending and economic growth. The regression equation Y = -3.54 + 1.78X confirms that public spending plays an important role in driving economic development in Makassar City.